Acute mesenteric ischaemia: the continuing difficulty in early diagnosis. Issue 807 (January 1993) - Heys, S. D.; Brittenden, J.; Crofts, T. J.
Abstract : Five cases of acute intestinal ischaemia due to occlusion of the superior mesenteric artery, all with a delay in diagnosis, are reported here. These cases illustrate the continuing difficulties, in clinical practice, in recognizing mesenteric ischaemia before intestinal infarction has occurred, despite the clinical awareness of this condition.